The Impact of the Digital Economy on Municipal Air Quality: Insights from Spatial Analysis - Yang, Xinyan; Yuan, Lijun (Asia Pacific Economic and Management Review, 2026)
Air quality is a core element concerning public health and sustainable development. As the backbone of new quality productive forces, the digital economy is quietly emerging as a significant driver of air quality improvement. Based on prefectural-level city data in China from 2020–2023, and after confirming the spatial correlation between the digital economy and air quality, this paper first employs bivariate Moran’s index to examine the spatial association characteristics between them. Subsequently, variance inflation factors are used to diagnose multicollinearity among annual variables. By constructing an ordinary least squares regression model, we investigate the overall impact effect. We then introduce a geographically weighted regression model to identify and estimate the spatial heterogeneity inherent in their relationship. Furthermore, the influence coefficient of the digital economy is utilized to analyze the spatial pattern and evolutionary trend of its impact on air quality. The results indicate a significant spatial dependence between the development of the digital economy and urban air quality, with this correlation pattern exhibiting a directional shift during the sample period. The geographically weighted regression model demonstrates superior goodness-of-fit and overall model adaptability compared to the ordinary least squares model, underscoring the robust spatial non-stationarity of the digital economy’s impact on air quality. Further analysis reveals a clear East-West differentiation pattern in the spatial distribution of the digital economy’s influence coefficients. This study not only provides spatial empirical support for exploring the complex relationship between the digital economy and environmental quality but also offers certain policy reference value for promoting regionally coordinated emission reductions and accelerating the green digitalization process.